Correlation Between Helicobacter pylori Infection, IgE Hypersensitivity, and Allergic Disease in Korean Adults. Issue 1 (25th September 2014) - Lee, Sang Pyo; Lee, Sun‐Young; Kim, Jeong Hwan; Sung, In‐Kyung; Park, Hyung Seok; Shim, Chan Sup; Moon, Hee‐Won
Abstract Background The correlation between allergic disease and Helicobacter pylori infection is still controversial in endemic areas. The aim of this study was to determine whether H. pylori infection is related to allergic disease and/or immunoglobulin E (IgE) hypersensitivity in Korean adults. Materials and Methods Consecutive Korean adults who visited our center for a routine checkup were enrolled. All subjects completed a questionnaire that was designed to ascertain their medical history pertaining to physician‐diagnosed allergic disease, allergy treatments, and H. pylori eradication therapy. Blood was sampled for serum anti‐H. pylori IgG antibody. IgE hypersensitivity was measured using a commercially available ImmunoCAP® Phadiatop (Phadia AB, Uppsala, Sweden). Results Of the 3376 Korean adults who were enrolled, 62 did not answer to the questionnaires adequately and were thus excluded. The proportion of noninfected subjects (p < .001) and the prevalence of IgE‐related allergic disease (p < .001) were both highest among those aged <40 years, while the prevalence of non‐IgE‐related allergic disease was highest among those aged ≥70 years (p < .001). Logistic regression analysis revealed that being younger than 40 years was significantly related to the absence of H. pylori infection (OR = 2.507, 95% CI = 1.621–3.878, p < .001). Conclusions The statuses of H. pylori infection, IgE hypersensitivity, and allergic diseases differ with age group, there being a higher prevalence of IgE‐related allergic disease and a lower H. pylori infection rate among young adults. The hygiene hypothesis might explain these findings in young Koreans, due to the rapid development and improvements in sanitation in Korea.